Glioblastoma Stem-Like Cells: Characteristics, Microenvironment, and Therapy - Yi, Yang; Hsieh, I-Yun; Huang, Xiaojia; Li, Jie; Zhao, Wei (Frontiers in Pharmacology, 2016)
Glioblastoma multiforme (GBM), grade IV astrocytoma, is the most fatal malignant primary brain tumor. GBM contains functional subsets of cells called glioblastoma stem-like cells (GSCs), which are radioresistant and chemoresistant and eventually lead to tumor recurrence. Recent studies showed that GSCs reside in particular tumor niches that are necessary to support their behavior. To successfully eradicate GBM growth and recurrence, new strategies selectively targeting GSCs and/or their microenvironmental niche should be designed. In this regard, here we focus on elucidating the molecular mechanisms that govern these GSC properties and on understanding the mechanism of the microenvironmental signals within the tumor mass. Moreover, to overcome the blood–brain barrier, which represents a critical limitation of GBM treatments, a new drug delivery system should be developed. Nanoparticles can be easily modified by different methods to facilitate delivery efficiency of chemotherapeutics, to enhance the accumulation within the tumors, and to promote the capacity for targeting the GSCs. Therefore, nanotechnology has become the most promising approach to GSC-targeting therapy. Additionally, we discussed the future of nanotechnology-based targeted therapy and point out the disadvantages that should be overcome.